2018
DOI: 10.1007/s10461-018-2036-2
|View full text |Cite
|
Sign up to set email alerts
|

Avoidant Coping Mediates the Relationship Between Self-Efficacy for HIV Disclosure and Depression Symptoms Among Men Who Have Sex with Men Newly Diagnosed with HIV

Abstract: HIV diagnosis presents a critical opportunity to reduce secondary transmission, improve engagement in care, and enhance overall well-being. To develop relevant interventions, research is needed on the psychosocial experiences of newly diagnosed individuals. This study examined avoidant coping, self-efficacy for HIV disclosure decisions, and depression among 92 newly diagnosed men who have sex with men who reported recent sexual risk behavior. It was hypothesized that avoidant coping would mediate the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 74 publications
(94 reference statements)
0
14
2
Order By: Relevance
“…This indicated the importance of passive coping for the relationship between self‐efficacy and illness acceptance, consistent with the conclusions of Phoenix and colleagues' work, which showed that higher self‐care self‐efficacy was related to decreased frequency of using maladaptive strategies, which in turn was associated with increased quality of life among PLWH in a structural model (Mo & Coulson, 2012). Regarding the size of the mediation effect, it was less than that for active coping in this study and far smaller than that in a previous study (Cherenack, Sikkema, Watt, Hansen, & Wilson, 2018), which found nearly a full mediation effect of avoidant coping. The potential reason might be that using passive coping strategies was always strongly related to negative adaptation outcomes (Kohn, 1996), such as depression, post‐trauma symptoms and stress (Bennett, Hersh, Herres, & Foster, 2016; Cherenack et al., 2018; Sikkema et al., 2013), but illness acceptance was a positive psychological adaptation outcome, strongly associated with active coping (Kohn, 1996).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…This indicated the importance of passive coping for the relationship between self‐efficacy and illness acceptance, consistent with the conclusions of Phoenix and colleagues' work, which showed that higher self‐care self‐efficacy was related to decreased frequency of using maladaptive strategies, which in turn was associated with increased quality of life among PLWH in a structural model (Mo & Coulson, 2012). Regarding the size of the mediation effect, it was less than that for active coping in this study and far smaller than that in a previous study (Cherenack, Sikkema, Watt, Hansen, & Wilson, 2018), which found nearly a full mediation effect of avoidant coping. The potential reason might be that using passive coping strategies was always strongly related to negative adaptation outcomes (Kohn, 1996), such as depression, post‐trauma symptoms and stress (Bennett, Hersh, Herres, & Foster, 2016; Cherenack et al., 2018; Sikkema et al., 2013), but illness acceptance was a positive psychological adaptation outcome, strongly associated with active coping (Kohn, 1996).…”
Section: Discussioncontrasting
confidence: 93%
“…Regarding the size of the mediation effect, it was less than that for active coping in this study and far smaller than that in a previous study (Cherenack, Sikkema, Watt, Hansen, & Wilson, 2018), which found nearly a full mediation effect of avoidant coping. The potential reason might be that using passive coping strategies was always strongly related to negative adaptation outcomes (Kohn, 1996), such as depression, post‐trauma symptoms and stress (Bennett, Hersh, Herres, & Foster, 2016; Cherenack et al., 2018; Sikkema et al., 2013), but illness acceptance was a positive psychological adaptation outcome, strongly associated with active coping (Kohn, 1996). The conclusions about the relationship between passive coping and illness acceptance should be approached with caution, given the cross‐sectional design of the study.…”
Section: Discussioncontrasting
confidence: 93%
“…A review of the literature shows that an association between age and depressive symptoms and substance use has been found among MSM living with HIV. 3,10,11 Age has been shown to be negatively associated with drug use. 11 However, this study was conducted in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Higher positive coping was associated with lower depressive symptoms [19]. Higher levels of HIV-related stigma and negative coping were associated with higher depressive symptoms [19,20]. CBSM can instruct patients to modify maladaptive cognitions such as HIV-related stigma, acquire social support, and engage in more adaptive behaviors such as positive coping to reduce depression and facilitate adjustment [21,22].…”
Section: Introductionmentioning
confidence: 99%